2017
DOI: 10.1172/jci85963
|View full text |Cite
|
Sign up to set email alerts
|

HDAC6-mediated acetylation of lipid droplet–binding protein CIDEC regulates fat-induced lipid storage

Abstract: Obesity is characterized by aberrant fat accumulation. However, the intracellular signaling pathway that senses dietary fat and leads to fat storage remains elusive. Here, we have observed that the levels of histone deacetylase 6 (HDAC6) and the related family member HDAC10 are markedly reduced in adipose tissues of obese animals and humans. Mice with adipocyte-specific depletion of Hdac6 exhibited increased fat accumulation and reduced insulin sensitivity. In normal adipocytes, we found that reversal of P300/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 41 publications
5
41
1
1
Order By: Relevance
“…Loss of HDAC6 in white adipose tissue leads to increased acetylation of the cell death-inducing DNA fragmentation factor subunit a-like effector C (CIDEC) protein, leading to increased lipid droplet storage (73), a change in lipid metabolism that could help explain the accelerated weight gain we saw. The combination of higher free fatty acids with overexpressed CIDEC in an earlier LDP model (13) plus its stabilization by HDAC6 absence provides a mechanism for enhanced lipid droplet accumulation (73), further supported by the hepatic steatosis observed in the HDAC6 deficient mice in this work. However, we also observed that HDAC6 loss alone was sufficient to change gut microbiota composition, independent of other factors.…”
Section: Discussionsupporting
confidence: 68%
“…Loss of HDAC6 in white adipose tissue leads to increased acetylation of the cell death-inducing DNA fragmentation factor subunit a-like effector C (CIDEC) protein, leading to increased lipid droplet storage (73), a change in lipid metabolism that could help explain the accelerated weight gain we saw. The combination of higher free fatty acids with overexpressed CIDEC in an earlier LDP model (13) plus its stabilization by HDAC6 absence provides a mechanism for enhanced lipid droplet accumulation (73), further supported by the hepatic steatosis observed in the HDAC6 deficient mice in this work. However, we also observed that HDAC6 loss alone was sufficient to change gut microbiota composition, independent of other factors.…”
Section: Discussionsupporting
confidence: 68%
“…Among the 10 proteins bound to Afadin preferentially in insulin‐stimulated conditions, we identified HDAC6, which was recently shown to modulate adiposity and insulin sensitivity as adipose tissue‐specific loss of HDAC6 promoted obesity and insulin resistance in mice . The interaction between HDAC6 and Afadin was confirmed by immunoprecipitation followed by Western blotting (Fig EV4B).…”
Section: Resultsmentioning
confidence: 57%
“…Further experiments are needed to dissect the mechanisms by which Afadin‐HDAC6 regulates acetylation and downregulation of the insulin receptor and the functional relevance of the Afadin/HDAC6/IR axis remains to be demonstrated. HDAC6 has recently been shown to regulate lipid droplet formation and thereby lipid storage in adipocytes affecting whole‐body metabolism , substantiating the importance of HDAC6 in adipose tissue biology.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Acetylation occurs on the ε-amino group of lysine residues (Lu et al, 2014). As a highly reversible protein modification process, acetylation is regulated by the action of histone acetylase and histone deacetylase (Guarente, 2011;Qian et al, 2017). The acetylation of proteins was first found in histones (Gu and Roeder, 1997); however, with the development of high-throughput mass spectrometry, many nonhistone acetylation processes and acetylated proteins have been identified in a variety of different species (Wilhelm et al, 1971;Glozak et al, 2005), including the silkworm (Nie et al, 2015;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%